Doping in elite cycling: a qualitative study of the underlying situations of vulnerability - Filleul, V.; d'Arripe-Longueville, F.; Pavot, D.; Bimes, H.; Maillot, J.; Meinadier, E.; Hauw, D.; Corrion, K. (Frontiers in Sports and Active Living, 2024)
Doping is considered a critical deviant behavior in competitive sports, and particularly in cycling, even though the phenomenon remains limited in sports in general. Previous qualitative studies have contributed to identify situations of vulnerability to doping in athletes. However, much of the research tends to focus on singular dimensions of vulnerability, such as physical or psychological aspects. The present study aimed to extend existing knowledge by concurrently exploring and attempting to categorize different types of situations of vulnerability that predispose elite cyclists to engage in doping. Ten high-level French-speaking doped cyclists were recruited (Mage = 49; SD = 14.63, two women). Semi-structured interviews were conducted. Both deductive and inductive thematic analyses were performed. Our results highlighted four types of vulnerability situations: (a) psychological (e.g., negative affects, maladaptive motivation, depression), (b) physical (e.g., exhaustion, impairments, injuries), (c) relational (e.g., organized doping, control, psychological or sexual harassment, social approval of doping), and (d) contextual (e.g., cycling culture, weather conditions, competitive stakes). By providing a clearer categorization of the situations of vulnerability that converge toward doping in sport, this comprehensive study allows for a holistic understanding of the various vulnerabilities. It paves the way for future research on related vulnerabilities and dispositional factors. Practically, it should also improve doping screening and prevention, and provide more favorable conditions for athletes.